Redesign and Improvement of Pottery Spinner to Increase Worker Producivity - I Made Agus Putrawan; I Gede Santosa; Ketut Adi (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
Many small industries produce handicrafts related to art in Bali, one of which is pottery. Pottery is an object made of clay which is formed and then burned to be a unique shape such as: jugs, glassware, cauldron, brazier, piggy bank, and other objects. The process of producing pottery required the complex steps, from preparing clay, printing by turning, drying and burning. The main difficulty of pottery producers is in the process of forming shapes which involved the rotating spinner. Most of small industries still use the manual spin control to rotate clay bucket holder. This research aims to re-design of a rotating spin machine from the existing pottery industries to increase the productivity. The sample was overtaken from 12 craftsmen in Singakerta Village, District of Ubud Gianyar, Bali. Sample P0 was given to craftsmen is still used the old design and P1 was given to sample modified and re-designed the old machine with added automatic control of rotating spinner. Workload is calculated based on the worker's pulse rate which is measured using a pulse meter. Research data were analyzed using descriptive and inferential statistics. T-test method was performed to analyzing the differences range between groups P0 and P1 at significance level of 5%. The results showed a workload was decreased from heavy to moderate by 12.09%. Production rate was increased by 282.1%, and productivity increased by 334.6%